Is there a balloon effect? Coca crops and forced eradication in Colombia (2019)
One explanation for the increasing number of hectares with coca cultivation is that eradication strategies displace coca crops but fail to completely clear affected areas. In the drug policy literature, that dynamic shifting is commonly known as the balloon effect. This study integrates georeferenced agricultural data through spatially explicit econometric models to tests the hypothesis that forced eradication generates spillover effects. Using annual data for 1,116 contiguous municipalities in Colombia between 2001 and 2010, we estimate a spatial Durbin model (SDM) with municipal and time fixed effects. At municipal level, we find no evidence of the balloon effect. Our results suggest that aerial eradication activities in a municipality reduce the new area under coca cultivation by 8 percent inside that municipality and by 3 percent in neighboring municipalities. Therefore, and contrary to the balloon effect hypothesis aerial eradication generates negative spillover effects. Our results provide deeper insights for policy design. In our analysis, we are able to distinguish between the change in coca cultivation as a result of eradication activities inside and outside the municipality.